A descriptive study of the effects and implications of proxemics to employees' behavior in a selected office - Tolod, Katrina R.
This study sought to determine vthe behavior of employees in an office environment by considering Proxemics as applied to the layout, placement, and circulation in the office space. It also investigated if these three categories are in line with the behavioral needs of the employees. This is a descriptive study that produced both qualitative and quantitative results. Non-probability purposive sampling was employed in the selection of the office environment and the respondents. To facilitate data gathering, survey questionnaires were given to seventeen respondents, who are all faculty members. The results of the study showed that the layout answers the employees' need of interaction with others but limits the need for privacy. The necessary distances to carry out social interactions based on Hall's (1966) theory of informal space were not considered in the layout of the office. Although there are intervening factors that may lessen the satisfaction of the employees in their workspace, positive responses were attained. The results of the study adhere to the man's perception of space based on its functionality. With regard to the circulation, the inaccessibility of other areas in the office was attributed to the improper clearances and width of aisles. The findings suggest that the layout, placement and circulation are not fully in line with the behavior of the employees of the office. It is recommended that design considerations be made with these categories that would support privacy and accessibility of spaces.